Measurement of Cell Migration on Surface-Bound Fibronectin Gradients - Smith, Jason T; Tomfohr, John K; Wells, Matthew C; Beebe, Thomas P; Kepler, Thomas B; Reichert, W. Monty (Langmuir, 2004)
A novel technique for the quantitative observation of cell migration along linear gradient substrates functionalized with adhesive proteins is presented. Gradients of the cell adhesion molecule fibronectin are generated by the cross diffusion of functionalizable alkanethiols on gold and characterized by X-ray photoelectron spectroscopy and surface plasmon resonance. Two distinct migration assays are described that characterize the movement of either sparsely populated noncontacting cells or a confluent monolayer of cells into free space. The drift speed of bovine aortic endothelial cells is measured and shown to increase along a fibronectin gradient when compared to a uniform control substrate using both assays. The results of these experiments establish reproducible conditions for studies of cell migration on gradients of surface-bound ligands.